PREVALENCE AND INTENSITY OF ECTOPARASITES ATTACK IN CRAB (Scylla serrata) IN SUNGAI GUNTUNG INDRAGIRI HILIR REGENCY - Saharudin, Saharudin; Yoswaty, Dessy; Nursyirwani, Nursyirwani (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACT Sungai Guntung has a potential for crabs because it still has fairly good mangrove forests in several areas. One of the problems found in the crab catchwas high mortality rate caused by disease and ectoparasites. This research aimed to determine the types of parasites that attack crabs and to determine the prevalence and intensity of ectoparasite attacks on crabs precisely and systematically. The field survey was conducted from April-May 2019 in Sungai Guntung waters, Kateman District, Indragiri Hilir Regency with sampling techniques from several fishermen to inventory ectoparasites on crabs.The observations found that ectoparasites include phylum protozoa namely Zoothamnium sp, and from arthropod phylum is Octolasmis sp.The prevalence value of ectoparasites infested Scylla serratawas Zoothamnium sp. 2.27%, Octolasmis sp. 80%, a mixture of Zoothamnium sp and Octolasmis sp. 6.67%. The intensity value of ectoparasites infested Scylla serrata was Zoothamnium sp. 9.5 ind/crab and Octolasmis sp. 149.23 ind/crab.Kata kunci :Ectoparasites, Crab, Protozoa, Prevalence, Intensity